The autophagic- lysosomal pathway determines the fate of glial cells under manganese- induced oxidative stress conditions - Gorojod, Roxana Mayra (2015)
Manganese (Mn) overexposure is frequently associated with the development of a neurodegenerative disorder known as Manganism. The Mn-mediated generation of reactive oxygen species (ROS) promotes cellular damage, finally leading to apoptotic cell death in rat astrocytoma C6 cells. In this scenario, the autophagic pathway could play an important role in preventing cytotoxicity. In the present study, we found that Mn induced an increase in the amount and total volume of acidic vesicular organelles (AVOs), a process usually related to the activation of the autophagic pathway. Particularly, the generation of enlarged AVOs was a ROS- dependent event. In this report we demonstrated for the first time that Mn induces autophagy in glial cells. This conclusion emerged from the results obtained employing a battery of autophagy markers: a) the increase in LC3-II expression levels, b) the formation of autophagic vesicles labeled with monodansylcadaverine (MDC) or LC3 and, c) the increase in Beclin 1/ Bcl-2 and Beclin 1/ Bcl-XL ratio. Autophagy inhibition employing 3-MA and mAtg5K130R resulted in decreased cell viability indicating that this event plays a protective role in Mn- induced cell death. In addition, mitophagy was demonstrated by an increase in LC3 and TOM-20 colocalization. On the other hand, we proposed the occurrence of lysosomal membrane permeabilization (LMP) based in the fact that cathepsins B and D activities are essential for cell death. Both cathepsin B inhibitor (Ca-074 Me) or cathepsin D inhibitor (Pepstatin A) completely prevented Mn- induced cytotoxicity. In addition, low dose of Bafilomycin A1 showed a similar effect, a finding that adds evidence about the lysosomal role in Mn cytotoxicity. Finally, in vivo experiments demonstrated that Mn induces injury and alters LC3 expression levels in rat striatal astrocytes. In summary, our results demonstrated that autophagy is activated to counteract the harmful effect caused by Mn. These data is valuable to be considered in future research concerning Manganism therapies.